PENGARUH RESPON AKSEPTOR TERHADAP KUALITAS PELAYANAN KELUARGA BERENCANA DI KABUPATEN PAMEKASAN - Saputri, Erina (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2017)
The National Family Planning Program which is part of the national development of the nation of Indonesia has a dual purpose that is to improve the welfare of mother and child and to realize a happy and prosperous small family. Along with this evaluation data on the quality of family planning services in Pamekasan District, it is known that family planning service has not fully utilized the service quality standard. Of 83% acceptors served, about 52% has not been initiated by the process of informed choice and informed concent. From 83% acceptors served, about 56% there has been no effort to provide post-service penyesomanFrom these data KB acceptors have not given a significant response in the process of family planning services, Region of Pamekasan had acceptors KB is quite significant with the community is very heterogeneous so it is very interesting to investigate. This research is included in the category of correlative quantitative (Correlation Quantitative), then the variables involved in these two studies there are two kinds, namely variables X and Variable Y. In this case including variable X is the response of KB Acceptor and Variable Y is Quality of KB service. Based on the results of research that has been implemented it can be concluded Influence of Response Acceptor Against Quality Family Planning Service In Region Pamekasan has a low response.